Neuroenhancement through cognitive training and anodal tDCS in multiple sclerosis. (February 2016) - Mattioli, Flavia; Bellomi, Fabio; Stampatori, Chiara; Capra, Ruggero; Miniussi, Carlo
Background: Cognitive training has been shown to improve cognitive function and quality of life in multiple sclerosis (MS) patients and is correlated with increased activity in the left dorsolateral prefrontal cortex (DLPFC). Objective: This study aims to test whether combining attention training with anodal transcranial direct current stimulation (a-tDCS) over the left DLPFC can improve training efficacy. Methods: Twenty patients impaired in attention/speed of information processing were randomly assigned to cognitive training during a-tDCS over the left DLPFC or cognitive training during sham tDCS for 10 daily sessions. Neuropsychological evaluations were conducted at baseline, after treatment and six months later. Results: When a-tDCS, rather than sham, was applied during the cognitive training, patients showed a significantly greater improvement in the Symbol Digit Modality Test (SDMT) and Wisconsin Card Sorting Test (WCST) after treatment ( p < 0.05) and in the Paced Auditory Serial Addition Test (PASAT) 2" and WCST six months later ( p < 0.05). They also had significantly shorter time to reach the most difficult exercise level, compared to sham treatment (6.3 vs. 7.4 sessions; p < 0.05). Conclusions: These results indicate that a-tDCS on the DLPFC during cognitive training fosters improvements in attention and executive function in MS patients and shortens treatment duration.